103 Young Adult's Sleep Efficiency is Positively Related to Risky Decision- Making in Novel BART. (3rd May 2021) - Duby, Nicole; Mizell, Jack Morgan; Huskey, Alisa; Wardle, Sophie Pinkston; Taylor, Daniel; Wilson, Robert
Abstract: Introduction: Numerous studies have indicated that poor sleep quality is relatively common among young adults and is related to less than optimal decision-making behavior. In order to assess decision-making behavior, we utilize a new variant of a Balloon Analogue Risk Task (BART) to assess sleep efficiency and other self-report measures' relation to risky decision-making in young adults. We hypothesize that individuals who have poorer sleep will make more risky decisions than those who have better sleep in a novel measure called the One-Shot BART. Methods: 200 undergraduate participants were recruited from the University of Arizona Psychology subject pool. Participants completed sleep quality questionnaires including the Sleep Condition Indicator and Split-Week Self-Assessment of Sleep-Y. Participants also completed a battery of self-report measures to assess exposure to traumatic events and trauma-related symptoms through the PTSD Checklist and Adverse Childhood Experiences Questionnaire. Lastly, participants were also tasked with completing a novel risk-taking task measure (the One-Shot BART) to assess risk-taking propensity and elucidate the cognitive processes underlying the risk-taking behavior. This task showed a significant correlation with (r=.24, p<.05) real-world risk measures from the RISQ assessment. Results: We found that better sleep efficiency showed a positive relationship with risk-taking(r=21, p<.05) in the BART, in conflict with our initial hypothesis that better sleep would lead to less risk-taking. However, in the BART some level of risk-taking is necessary to do well in the task, so risk-taking is beneficial. We found that those people with lower levels of sleep efficiency also performed more randomly in the BART (p<.05), showing that a lack of sleep affects noise in the decision process, which is also supported by our finding showing that people with lower sleep efficiency also show a higher level of response time variability (p<.05). Conclusion: Behavioral results from the One-Shot BART are affected by Sleep Efficiency in a college student population. Interestingly, Sleep Efficiency was positively correlated with risky decision making in the One-Shot BART, indicating more optimal risk-taking in the game that may be mirrored in real-world decisions. Support (if any):